The Effect of Implementing Local Government Information System on the Quality of Local Government Financial Reports Moderated by Human Resource Competence - Naida, Nasrun; Amir , Andi Mattulada; Din, Muhammad; A, M. Ikbal; Karim, Fikry (Journal of World Science, 2023)
This study aims to measure the effect of implementing local government information systems on the quality of government financial reports with human resource competence as a moderating variable. The research was conducted using quantitative methods, and data collection was carried out using questionnaires and PLS with the help of WarpPLS software. The results of this research analysis show empirical evidence that the implementation of local government information systems on the quality of local government financial reports can have a positive effect; on the other hand, human resource competence can moderate the relationship between the application of local government information systems to the quality of local government financial reports. Studies This gets empirical proof about many matters related to quality report finance government area. System information government area own influence positive to quality report finances. Competence source Power man can strengthen influence connection between information systems government area to quality report finance government area.